Economic Feasibility of Solar Irrigation Pumps in Southern Region of Bangladesh (Bangladesh Journal of Agricultural Research, 2023)
This study presents the economic suitability of solar pump in the southern region of Bangladesh. Field survey was conducted during 2018-19 at Kalapara and Galachipa Upazila of Patuakhali district, Borguna Sadar and Amtoli Upazila of Borguna district, Charfassion and Lalmohon Upazila of Bhola district. BARI developed large and mini solar pumps and were tested in those areas for irrigation in vegetables. Two water saving irrigation techniques (Drip and alternate furrow) and one conventional irrigation practice were used for cultivating tomato, brinjal, watermelon and chili. The internal rate of return of all irrigation systems were greater than the bank interest rate. Solar powered drip and alternate furrow irrigation system was found more profitable than low lift pump for cultivation of vegetables. The benefit-cost ratio of mini and large solar systems were found 1.50 and 1.42, respectively. So, solar pump may be recommended for irrigation vegetables in the southern region of Bangladesh.Bangladesh J. Agril. Res. 47(2): 241-255, June 2022